2014
DOI: 10.1097/brs.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Evaluation of the Suture Anchors Used in Open-Door Laminoplasty

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Second, double-door laminoplasty allowed for the intraoperative observation of the spinal cord, directly or using ultrasonography, after the decompression. Third, in cases where suture anchors are used in cervical laminoplasty, the loads on suture anchors are thought to be lower in double-door laminoplasty than in open-door laminoplasty because of the shorter lever arm of the split lamina, as reported by us [14], and so there may be less possibility of implant failure and lamina closure in double-door laminoplasty than open-door laminoplasty. The present study has some limitations.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, double-door laminoplasty allowed for the intraoperative observation of the spinal cord, directly or using ultrasonography, after the decompression. Third, in cases where suture anchors are used in cervical laminoplasty, the loads on suture anchors are thought to be lower in double-door laminoplasty than in open-door laminoplasty because of the shorter lever arm of the split lamina, as reported by us [14], and so there may be less possibility of implant failure and lamina closure in double-door laminoplasty than open-door laminoplasty. The present study has some limitations.…”
Section: Discussionmentioning
confidence: 83%
“…However, few studies have closely investigated the validity of suture anchor use in cervical laminoplasty. We previously investigated the mechanical loads on suture anchors in cervical laminoplasty, and showed that all loads during cervical motion were much lower than the failure loads of the suture anchor [14]. However, this previous study was a cadaveric study, where the cervical spine was moved passively.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We have designed a contralateral “Zhang’s portal” to facilitate cervical canal decompression ( 18 ), therefore, we have rich experience in bilateral biportal operations. Kurokaw ( 19 ) demonstrated the validity of suture anchors in cervical laminoplasty in a cadaveric study, and we successfully performed suture anchor fixation on the contralateral side using the UBE technique. Compared with open surgery, continuous irrigation not only ensures a clear operative field, but also lowers the risk of infection ( 7 , 20 ).…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, Khan, et al 11 reported the utility and ease of using the suture-anchor system. 12 Kurokawa, et al 13 reported the validity of using suture anchors in laminoplasty. Hu, et al 14 conducted a study to compare open-door laminoplasty between patients with anchors on the hinge side and patients with titanium miniplates.…”
Section: Discussionmentioning
confidence: 99%